Financial Liberalization and Financial Development in Nepal - Bhetuwal, Khem Raj (NRB Economic Review, 2007)
An efficient financial system can effectively mobilize and allocate resources leading to robust economic growth. Financial liberalization improves the functioning of financial system by increasing the availability of funds and allowing risk diversification and increased investment. The indices of financial liberalization and financial development, generated by the principal component analysis, depict a gradual process of financial liberalization and a continuous financial sector development. The paper finds the presence of bi-directional causal relationship between the liberalization of financial sector and level of financial development in Nepal.